Three new species of eriophyoid mites (Acari: Eriophyoidea) infesting fruit yielding plants from India - Chakrabarti, Samiran; Sarkar, Sanjay (Zootaxa, 2011)
Three new species of eriophyoid mites namely Aculops spondiasis n. sp. infesting Spondias pinnata Kurz. (Anacardiaceae), Phyllocoptruta citricola n. sp. infesting Citrus maxima (J. Burm.) (Rutaceae) and Tegonotus fisus n. sp. infesting Mangifera indica (L.) (Anacardiaceae) are described from India. Relationships of new species with other eriophyoid species are also provided.